Improving Aetiological Diagnosis of Travellers’ Diarrhoea Using Multiplex PCR Gastrointestinal Panels: A Retrospective Cross-Sectional Study from a High-Travel Tropical Setting - Bryananda -; Linda -; Ni Made Ari Kurnianingrum (The Indonesian Society for Digestive Endoscopy, 2026)
Background: Travellers’ diarrhoea is a leading cause of acute gastroenteritis (AGE) worldwide. In Indonesia, diagnosis still relies largely on conventional stool microscopy despite its limitations, while access to multiplex PCR gastrointestinal (GI) panels remains limited. This study provides an early comparison between multiplex PCR and routine stool microscopy for AGE in a high-travel setting in Indonesia.Methods: A retrospective cross-sectional study of patients presenting with AGE was conducted at a private international hospital in Bali (January 2024-June 2025). All patients underwent stool microscopy and multiplex PCR GI panel testing. Descriptive, bivariate, and multivariable analyses assessed patient characteristics, pathogen distribution, and associations with microscopy findings.Results: A total of 114 patients were included (mean age 36.1 ± 14.4 years; 55.3% male). Multiplex PCR detected bacterial pathogens in 88.6% of cases, viral pathogens in 41.2%, and parasitic pathogens in 3.5% of cases. The most common bacteria were enteropathogenic Escherichia coli (47.4%), enteroaggregative E. coli (28.1%), and Campylobacter spp. (26.3%), while norovirus (11.4%) predominated among viruses. Routine stool microscopy parameters showed no meaningful association with bacterial or viral detection. Importantly, erythrocytes were independently associated with lower odds of viral infection (AOR 0.09; 95% CI 0.01–0.71) and higher odds of parasitic infection (AOR 8.16; 95% CI 1.05–63.41).Conclusion: Multiplex PCR substantially improves pathogen detection and clarifies the microbial profile of travellers’ diarrhoea in Bali. Although stool microscopy has limited diagnostic value, the presence of erythrocytes may provide a useful interpretive clue when molecular diagnostics are unavailable